Rutherford Backscattering Spectroscopy Study of Thin Films with (Sm + Eu) Complexes - Reyes, Reynaldo (2016)
In this work we report the use of Rutherford backscattering spectroscopy (RBS) for the analysis, search of contaminants and measurements of thickness of the organic-lanthanide [SmxEuy(TTA)3(TPPO)2] thin films used as light-emitting layer in organic light-emitting diodes (OLEDs). Also a study of photoluminescence of the films [SmxEuy(TTA)3(TPPO)2] is realized, and it is found that the emission of light of the mixture is carried out independently for the molecules [Sm(TTA)3(TPPO)2] and [Eu(TTA)3(TPPO)2], not being observed a intermolecular energy transfer between these molecules.